2018
DOI: 10.1186/s12978-018-0539-y
|View full text |Cite
|
Sign up to set email alerts
|

‘It’s because I like things… it’s a status and he buys me airtime’: exploring the role of transactional sex in young women’s consumption patterns in rural South Africa (secondary findings from HPTN 068)

Abstract: Background‘Transactional sex’, defined as a non-marital, non-commercial sexual relationship in which money or material goods are exchanged for sex, is associated with young women’s increased vulnerability to HIV infection. Existing research illustrates that the motivations for transactional sex are complex. The fulfilment of psycho-social needs such as the need to belong to a peer group are important factors underlying young women’s desires to obtain certain consumption items and thus engage in transactional s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
16
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 56 publications
3
16
0
Order By: Relevance
“…partner age or transactional nature of relationship). These findings are consistent with findings from another qualitative investigation undertaken as part of the HPTN 068 cash transfer study, showing that transactional sex was often motivated by love or social status, rather than basic needs (Ranganathan et al 2018). Quantitative findings from the HPTN 068 main trial found similar results, with impacts on having a sex partner in the last 12 months and unprotected sex in the past 3 months, but not transactional sex or age-disparate partnerships (Pettifor, MacPhail, Hughes et al 2016;Stoner et al 2017;Stoner et al 2018).…”
Section: Discussionsupporting
confidence: 85%
“…partner age or transactional nature of relationship). These findings are consistent with findings from another qualitative investigation undertaken as part of the HPTN 068 cash transfer study, showing that transactional sex was often motivated by love or social status, rather than basic needs (Ranganathan et al 2018). Quantitative findings from the HPTN 068 main trial found similar results, with impacts on having a sex partner in the last 12 months and unprotected sex in the past 3 months, but not transactional sex or age-disparate partnerships (Pettifor, MacPhail, Hughes et al 2016;Stoner et al 2017;Stoner et al 2018).…”
Section: Discussionsupporting
confidence: 85%
“…This decrease in the frequency of material items might be as older women are more financially independent and hence have more resources, are in longer term relationships and so do not expect gifts as often, or as they have become better at negotiating condom use with age. Therefore, as young women age and transition into a different stage of life, these findings may reflect changes in their primary motivations around obtaining items to improve their status and to satisfy feelings of needing to belong [ 26 ]. More research is needed to understand the evolving nature of transactional sex as young women age and transition into adulthood.…”
Section: Discussionmentioning
confidence: 99%
“…Yet adolescents’ psycho-social needs for a modern lifestyle (e.g. smart phone and data), may not be easily met by the jobs they do; this could increase their vulnerability to transactional sex and exposure to STIs [ 36 ]. Adolescents who work but do not receive pay, in addition to those who are self-employed in agriculture and in manual jobs receive little to no pay [ 37 ] which increases the vulnerability of these female adolescents.…”
Section: Discussionmentioning
confidence: 99%
“…The female adolescents who do not work could face similar vulnerability, however, the reduced risk of STIs could be attributed to the gains from parental monitoring [ 39 ], which is not possible for adolescents who may be working outside the home or away from parents. An alternative explanation could be, that adolescents who already have developmental problems may use work to gain access to behaviours that would be confined to only adults, including sexual behaviours and drug use, increasing exposure to peer groups that may lead them to engage in risky sex and STIs [ 36 , 39 ]. Mortimer [ 18 ] argues that this could occur as a result of self-selection, however, the fact that adolescents who worked without receiving renumeration also reported increased odds of STIs suggests that their vulnerability over and above self-selection effects may be the reason for this relationship.…”
Section: Discussionmentioning
confidence: 99%